2015
DOI: 10.1111/gcb.13029
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting impacts of continuous moderate drought and episodic severe droughts on the aboveground‐biomass increment and litterfall of three coexisting Mediterranean woody species

Abstract: 26Climate change is predicted to increase the aridity in the Mediterranean Basin and 27 severely affect forest productivity and composition. (P. latifolia). However, the results of this long-term study also suggest that the effect 47 of drought treatment has been dampened over time, probably due to a combination of 48 demographic compensation, morphological and physiological acclimation and 49 epigenetic changes. However, the structure of community (e.g. species composition, 50 3 dominance and stand density)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 70 publications
(165 reference statements)
8
93
0
1
Order By: Relevance
“…This reduction was not accompanied by a reduction in sapwood area, and thus the ratio of leaf to sapwood area was decreased at the shoot level (Limousin, Longepierre, et al 2010;Limousin et al 2012), indicating that tree-level transpiration was reduced by decreasing the transpiring (leaf) area, which is also in agreement with the long-term increase in leaf litterfall in the drought treatment observed in Prades (Liu et al 2015). Indeed, leaf-specific conductivity has increased in the long term in droughted plants as a consequence of a decrease in the ratio of leaf to sapwood area (MartinStpaul et al 2013).…”
Section: Trends Of Crown Defoliation and Their Relationship With Drousupporting
confidence: 77%
See 2 more Smart Citations
“…This reduction was not accompanied by a reduction in sapwood area, and thus the ratio of leaf to sapwood area was decreased at the shoot level (Limousin, Longepierre, et al 2010;Limousin et al 2012), indicating that tree-level transpiration was reduced by decreasing the transpiring (leaf) area, which is also in agreement with the long-term increase in leaf litterfall in the drought treatment observed in Prades (Liu et al 2015). Indeed, leaf-specific conductivity has increased in the long term in droughted plants as a consequence of a decrease in the ratio of leaf to sapwood area (MartinStpaul et al 2013).…”
Section: Trends Of Crown Defoliation and Their Relationship With Drousupporting
confidence: 77%
“…30% of the throughfall reduced soil moisture by an average of 13% in the drought-treatment plots in Prades (Liu et al 2015). An analogous reduction of ca.…”
Section: Trends Of Crown Defoliation and Their Relationship With Droumentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, there is evidence of differential sensitivity among plant genotypes [37,38], species [9,[39][40][41] and functional groups [4,42,43] to climate extremes. Liu et al [44] observed large variation in long-term drought impacts to tree growth depending on the species considered in Mediterranean forest communities, with fruit production and growth largely impacted in certain species and others not affected. Similarly, Hoover et al [4] observed differential sensitivity to repeated droughts and heatwaves between the C 3 and C 4 co-dominant plant species.…”
Section: Scaling Individual Plant Responses To the Population And Commentioning
confidence: 99%
“…It has been reported that drought and warming can advance the spring growing season, affect reproductive performance and decrease plant productivity of E. multiflora [63,64]. The drier and warmer conditions projected for the future could affect diversity, decrease biomass and increase mortality in Mediterranean ecosystems [11,18,21,65]. Additionally, warmer conditions generally imply that plants need more water due to higher transpiration.…”
Section: Pri Assessment Of Seasonal Photosynthesis Under Long-term Drmentioning
confidence: 99%